Toxisitas temephos, minyak atsiri jahe ​(Zingiber officinale Roxb)​, dan ​Bacillus thuringiensis ssp. israelensis​ (Bti) terhadap larva nyamuk ​Ae. aegypti​ dari Sumatra Utara - Horas Sihotang; Sitti Umniyati (Berita Kedokteran Masyarakat (BKM), 2018)
Toxicities of temephos, essential oil of ginger (Zingiber officinale Roxb), and Bacillus thuringiensis ssp. Israelensis (Bti) against Ae. aegypti larvae from North Sumatra  PurposeThe purpose of this study was to confirm the resistance status and resistance ratio (RR) of  Ae. aegypti larvae to temephos as well as to determine the effectiveness of a liquid solution of Bti H-14 and the essential oil of ginger (Zingiber officinale roxb) against Ae. aegypti larvae from Deli Serdang, North Sumatra.MethodA randomized post-test only control group was con- ducted using 3rd instar larvae of Ae. aegypti as the subjects of this study. Larval mortality was recorded after 24 hours of exposure with diagnostic dose of temephos (0.02ppm) to determine the resistance status. Probit analysis was conducted to determine median lethal time (LT50) and the RR. The concetration of Bti toxicity test was 0.01, 0.013, 0.017, 0.02, 0.03 and 0.04 mL/L and the concentration of toxicity essential oil of ginger test was 66.6, 99.9, 133.2, 166.5, 199.8 and 266.4 ppm.ResultsAe. aegypti larvae were resistant to temephos (0.02ppm) with RR 1.9 < 5. The value of LC50 and LC90 of Bti were 0.014; 0.024 mL/L respectively. The value of LC50 and LC90 of essential oil of ginger solution were 65.6ppm and 129.1ppm respectively.ConclusionLarvae are resistant to temephos with low resistance criteria. Bti and essential oil of ginger are toxic to Ae. aegypti larvae.